Versatility, reliability and efficiency. Universal Adhesive System «Futurabond U» (VOCO) - Symonenko, R. (Actual Dentistry, 2018)
Resume. Modern dentistry offers a practical doctor a huge selection of adhesive systems, but not all systems provide the same durability of restorations. One of the main ways of development of adhesive dentistry in recent years is the concept of self-etching, which excludes the classical stage of etching tooth tissues with acid followed by its rinsing. Neutralization of the acid occurs due to the reaction with hydroxyapatites of hard tooth tissues. These are adhesive systems of VI and VII generations. Conclusions. According to the results of our survey, it was found that 80 % of respondents were correctly aware of the method of application of IV and V generation adhesives, 48 % of the VI generation and only 42 % of the VII generation. At the same time 79 % of doctors do not know what is the difference in the use of ethanol and acetone-containing adhesives. Key words: adhesive stomatology, self-etching, universal adhesive system, «Futurabond U».